Definition- Notional Genesis of Methodic Accompaning of Aesthetic Personality Upbringing - Yatsyshyn, Roman (Pedagogical Discourse, 2012)
Distinct features of the definition in the content of aesthetic education, its main points and trends during the second part of the 20-th century are analyzed in the article.